Analisis Pengaruh Brand Awareness dan Perceived Value terhadap Purchase Intention pada Live Shopping - Mervin Mervin; Diah Priharsari; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Information technology is currently developing very rapidly so that several e-commerce and social media companies have created a new live video-based platform called live shopping. Currently live shopping is used as a means of buying and selling online and of course through this platform it is hoped that it will be able to increase public buying interest. However, to be able to increase buying interest, streamers or broadcasters need to pay attention to the factors that influence consumers' purchase intentions for a product, namely trust in the product. Trust in the product or trust in the product is also driven by brand recognition or brand awareness and perceived value. This study aims to find out how brand awareness and perceived value affect trust in products and to find out the effect of trust in products on purchase intentions or consumer purchase intentions. This study used the Structural Equation Model - Covariance Based (SEM-CB) method and obtained clean data for 433 respondents. From the research conducted, it was found that the hypothesis was not accepted, namely brand awareness had an effect on trust in products with a p(probability) value of 0.394 and there was an accepted hypothesis, namely perceived value had an effect on trust in products with a p(probability) value <0.001 and the trust hypothesis product has an effect on purchase intention with a value of p(probability) < 0.001.